Dinickelaferrocene: A Ferrocene Analogue with Two Aromatic Nickeloles Realized by Electron Back‐Donation from Iron. Issue 34 (3rd July 2020) - Huang, Zhe; Zheng, Yu; Zhang, Wen‐Xiong; Ye, Shengfa; Deng, Liang; Xi, Zhenfeng
Abstract: The first example of ferrocene analogues with two transition‐metal metallole ligands of the general formula ( η 5 ‐C4 R4 M)2 Fe in a sandwich structure are reported. Specifically, dinickelaferrocene 2, a type of dimetallametallocene, is efficiently synthesized from the reaction of dilithionickelole 1 with FeBr2 or FeCl2, presumably via a redox process, and is subjected to detailed experimental (single‐crystal X‐ray structural analysis, ICP‐OES, magnetometry, 57 Fe Mössbauer, XPS) and theoretical (MOs, CDA, NICS, ICSS, and AICD) characterizations. Unlike ferrocene and its Cp ligands, the aromaticity of dinickelaferrocene and its nickelole ligands is accomplished by electron back‐donation from the Fe 3d orbitals to the π* orbitals of nickelole. Taken together, this work describes a new class of metallaferrocene sandwich complexes and provides a novel approach to effect aromaticity that will contribute to further development of metallocene chemistry. Abstract : A different origin of aromaticity : Dinickelaferrocene was realized as the first example of a transition‐metal dimetallaferrocene. The nickelole ligands act as non‐innocent ligands and accept electron density from Fe via back‐donation to achieve aromaticity.